Peningkatan Pengetahuan Remaja Putri Tentang Penanganan Disminore Primer - Khayati, Yulia Nur; Veftisia, Vistra; Widyaningsih, Ari; Windayanti, Hapsari; Dewi, Maya Kurnia; Hidayanti, Nur; Sari, Putri Ayuni; Rinawati, Rinawati (UNIVERSITAS NGUDI WALUYO, 2021)
Menstruation happens when body discharges blood from the uterus periodically accompanied by desquamation of endometrium (Prawirohardjo, 2009). In general, this phase will occur normally, but in some individuals, it becomes a painful condition and interferes their activities called as dysmenorrhea. According to the World Health Organization (WHO), the average incidence of dysmenorrhea in the world is 16.8 - 81%. In Indonesia, the prevalence of dysmenorrhea in 2008 reached 64.25% consisting of 54.89% primary dysmenorrhea and 9.36% secondary dysmenorrhea. The incidence of dysmenorrhea is felt to be disturbing experienced by 50% of those at reproductive age, and 60-85% in teenagers (Keisya, 2009).Until now, the problem that often arises is the lack of knowledge of female teenagers in dealing with primary dysmenorrhea. In connection with the problem, an online education about it as an activity of community empowerment was conducted attended by 33 female teenagers. This activity was carried out in 3 stages; first by choosing the teenagers according to the target decided before, second by conducting a pre-test about dysmenorrhea followed by giving the digital information about dysmenorrhea and doing a post-test about dysmenorrhea, and third by evaluating the knowledge of the female teenagers about dysmenorrhea continued by giving the result of the evaluation to the party cooperated with this activity. The results of this activity is shown by the increase of knowledge of the female teenagers after getting the education about how to handle primary dysmenorrhea. AbstrakMenstruasi atau haid adalah pengeluaran darah secara periodik dan siklik dari uterus, disertai dengan pelepasan (deskuamasi) endometrium (Prawirohardjo, 2009). Secara umum fase ini akan berlangsung dengan normal, namun pada beberapa individu menjadi suatu keadaan yang sangat berat dan mengganggu aktivitas (dismenore). Menurut World Health Organization (WHO) menyatakan bahwa rata-rata insidensi dismenore didunia sebesar 16,8 – 81%. Di Indonesia Prevalensi dismenore tahun 2008 mencapai 64.25 % yang terdiri dari 54,89% dismenore primer dan 9,36% disminore sekunder. Kejadian dismenore dirasakan mengganggu yaitu sebanyak 50% pada usia reproduksi, dan 60-85% pada remaja (Keisya, 2009).Sampai saat ini permasalahan yang sering muncul adalah kurangnya pengetahuan remaja putri dalam menangani dismenorea primer. Berkaitan dengan permasalahan mitra tersebut maka kami melakukan pengabdian kepada masyarakat tentang optimalisasi pemahaman dalam menangani dismenorea primer dengan cara daring melalui WA Group yang diikuti oleh 33 remaja putri.Pengabdian ini dilaksanakan dalam 3 tahap yaitu Tahap Pertama adalah pemilihan sasaran remaja putri, Tahap Kedua adalah melakukan pre test tentang dismenorea, pemberian informasi digital tentang dismenorea,dan melakukan post test tentang dismenorea Tahap Ketiga adalah evaluasi pengetahuan remaja tentang dismeorea dan memberikan hasil pelaksanaan kepada mitra pengabdian. Hasil dari pengabdian digambarkan dengan peningkatan pengetahuan remaja setelah dilakukan penyuluhan tentang penanganan disminore primer.